[GaF(H2O)][IO3F]: a promising NLO material obtained by anisotropic polycation substitution. Issue 27 (9th June 2021) - Huang, Qian-Ming; Hu, Chun-Li; Yang, Bing-Ping; Fang, Zhi; Lin, Yuan; Chen, Jin; Li, Bing-Xuan; Mao, Jiang-Gao
Abstract : A novel salt-inclusion fluoroiodate nonlinear optical material, [GaF(H2 O)][IO3 F], is derived from CsIO2 F2 through polycation substitution, and it exhibits an intense SHG effect of 10 times that of KH2 PO4 and improved overall performance. Abstract : A novel salt-inclusion fluoroiodate [GaF(H2 O)][IO3 F] derived from CsIO2 F2 was ingeniously obtained through anisotropic polycation substitution. Because the catenulate [GaF(H2 O)] 2+ framework serves as a template for the favorable assembly of the polar [IO3 F] 2− groups and contributes to the nonlinear coefficient, [GaF(H2 O)][IO3 F] exhibits a greatly improved second-harmonic generation (SHG) effect of 10 times that of KH2 PO4 (KDP) and a considerable band gap of 4.34 eV compared to the parent compound CsIO2 F2 (3 × KDP, 4.5 eV). Particularly, to the best of our knowledge, [GaF(H2 O)][IO3 F] has the largest laser-induced damage threshold (LDT) of 140 × AgGgS2 of the reported iodates. All these results signify that [GaF(H2 O)][IO3 F] is a promising nonlinear optical (NLO) crystal. This work also proposes that anisotropic polycation substitution is an effective approach to optimize the SHG effect and develop excellent NLO materials.